The stress test, differences in the physiological response between sedentary and recreational athletes - Hernández-Pacheco, Guadalupe; Cano, Víctor; Armendáriz-González, Gilberto; Valencia-Cañedo, Cesar A; Martínez- Rosas, Martín (Horizonte Sanitario, 2025)
Objective: Compare the physiological response between sedentary and recreational athletes during the stress test. Materials and Methods: An analytical cross-sectional study was carried out; sedentary male volunteers and recreational athletes were included. A stress test was performed with the modified Bruce protocol on a ramp. Statistical analysis. A descriptive analysis of the variables was carried out, and the difference between groups was evaluated usingthe t-test and the nonparametric Wilcoxon and Kruskal-Wallis tests. The value of p<0.05 was considered statistically significant. Results: Both groups achieved maximum effort, and there were no differences in age, weight, height, and body mass index between groups. At maximum effort, athletes showed lower diastolic blood pressure (p=0.0007),and higher peak oxygen volume (p=0.002) than sedentary subjects.Sedentary subjectsreached maximum effort in less time(p=0.002). The pressor and chronotropic response in the athletes was lower (p=0.001 and p=0.004 respectively), while the anaerobic threshold was higher (p=0.001) compared to sedentary subjects. Conclusions: This study shows that the stress test allows a non-invasive evaluation of the body´s response to exercise, demonstrating the advantages of doing it even at a recreational level and the negative changes in sedentary people. Keywords: Sport; Physical exercise; Heart; Health.